2019
DOI: 10.1186/s40981-019-0260-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of labor epidural analgesia on labor, delivery, and neonatal outcomes: a propensity score-matched analysis in a single Japanese institute

Abstract: Purpose: Lumbar epidural analgesia (LEA) is the most widely used method in reducing labor pain. Previous RCTs have shown that LEA does not increase cesarean section rates; however, the results are inconsistent and may vary depending on the different backgrounds. Therefore, we aimed to study whether LEA would affect the course of labor in our institute. Methods: Delivery records from October 2013 to April 2016 were collected. Deliveries at gestational age < 36 weeks and multiple pregnancies were excluded. All c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 12 publications
3
14
1
Order By: Relevance
“…There was no difference between the groups (P=0.05, OR 1.57, 95% CI 0.99 to 2.49) Herrera-Gomez et al 8 and Greenwell et al 34 observed the increased need for any assisted ventilation in the EA group. Antonio et al 7 and Naito et al 58 looked for the need for advanced resuscitation and did not find any difference between the groups.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There was no difference between the groups (P=0.05, OR 1.57, 95% CI 0.99 to 2.49) Herrera-Gomez et al 8 and Greenwell et al 34 observed the increased need for any assisted ventilation in the EA group. Antonio et al 7 and Naito et al 58 looked for the need for advanced resuscitation and did not find any difference between the groups.…”
Section: Discussionmentioning
confidence: 95%
“…Majority of previous studies had similar observation. 7,17,18,[56][57][58] Hintz et al 59 and Tawhid Soderholm et al 15 found a decrease in cord arterial pH <7.1 in association with EA. One study 19 observed better cord pH in patients with EA.…”
Section: Discussionmentioning
confidence: 98%
“…Another study has also shown second-stage labor prolongation with the use of epidural analgesia [ 10 ]. A study by Naito et al demonstrated increased duration of both the first and second stages of labor with epidural analgesia [ 20 ]. Cochrane review by Anim-Somuah et al demonstrated longer first and second stages of labor with increased chances of oxytocin augmentation in an epidural group than in the opioid group [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…32 Maternal age, maternal body mass index, obesity, and epidural analgesia are some risk factors for cesarean section depending on prolonging labor. [33][34][35][36] The present study's primary purpose was to determine fetal adipose tissue components' effect on labor progression by excluding other risk factors that cause prolongation. We planned to see the effect of fetus soft tissue components on the diagnosis of labor protraction or arrest.…”
Section: Discussionmentioning
confidence: 99%